Electrical Transport in Disordered Sheet Networks and Viscoelastic Properties of Nanosheet Suspensions - Venkatraman, Arvind (Trinity College Dublin. School of Physics. Discipline of Physics, 2025)
The rise of printed electronics using 2D nanomaterials has increased the focus on optimizing nanosheet ink formulations. These formulations are vital for applications like transistors, conductive fillers in composites, and supercapacitor electrodes, among others. Key parameters for optimization include the network volume fraction Φ, nanosheet dimensions, and their electrical properties. Despite the excellent electrical properties and feasible production of 2D nanomaterials, the electrical conductivity of the printed networks is largely lower than that of an individual nanosheet. For the same material, conductivity has been reported to vary over a broad range depending on the nanosheet production as well as deposition method. Higher volume fractions lead to reduced interparticle junction resistances but the exact relationship between volume fraction and electrical conductivity remains an open question for these systems. In the first part of this thesis, we introduce a model system using high aspect ratio metallic flake packing systems as a way to study the electrical properties of nanosheet networks. We present a semiempirical model and show that the ratio of the in-plane to out-of-plane conductivity follows a Φ2 relationship and is dependent on the flake dimensions. Further, we observe that the electrical resistance of the flake packings has a power-law relationship with the applied pressure with an exponent of -1. We proceed to validate our model prediction by simulating a resistor network and observe reasonably good agreement in the overall trend with a prefactor difference, which may be due to the presence of hotspots. Because of their high surface area, good structural integrity, and improved printability, high-viscosity nanosheet inks are extensively used to produce battery electrodes or energy storage devices. In spite of several excellent rheological and printability studies of non-Newtonian nanosheet suspensions, there is a lack of knowledge about the shear-history dependence exhibited by these nanoinks. In the second part of this work, shear-thinning aqueous inks made from graphene oxide (GO), which display good mechanical properties and stability in water, are used to investigate how an applied pre-shear rate affects the viscoelastic properties of these yield stress fluids. We show that large residual stresses are encoded in the microstructure at low shear rates and vice versa after flow cessation. In addition, we show that the shear modulus at a single concentration varies by a factor of approximately 4, indicating a possible tool/protocol to tune the rheology of these 2D colloidal suspensions for additive manufacturing applications. The variation in the shear modulus exhibits a concentration-independent correlation with the residual stress. Finally, we demonstrate that the yielding behaviour of these yield-stress fluids conforms to a widely accepted universal trend shown by a broad class of materials, characterized by a critical yield strain of 3.49±0.31%.
APPROVED
Keywords: Electrical Transport; Conductivity; Disordered Sheet Networks; Flake Packing; Volume Fraction; Nanosheet Suspensions; Viscoelastic Properties; Shear-history; Rheology; Viscosity; Yield-stress Fluids